2019
DOI: 10.1142/s2339547819300014
|View full text |Cite
|
Sign up to set email alerts
|

Emerging micro and nanotechnologies in neuroscience: Devices, fabrication methods, and implementation in monitoring of neural activity and drug delivery

Abstract: Neural activity that occur during motor movement, speech, thought, and various other events can be observed in the form of brainwaves composed of synchronized electrical pulses emitted from adjoining communicative neurons. Observations of these brainwaves have been made possible through neurodevices, which can detect changes in electrical and/or mechanical parameters. For decades, the field of neuroscience has been enriched by the utilization of neurotechnologies at the microscale, which has begun to gain furt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 267 publications
0
4
0
Order By: Relevance
“…Specific reagents, such as pharmacological agents or fluorescent dyes, can be dissolved in the reservoir fluid, either by not reaching their optimal concentration or by constantly exposing brain slices to these stimulations. There are brain-on-a-chip devices [ 29 , 30 , 31 ] focused on localized drug application for brain-on-a-chip, but the alternatives for this application in brain slice-on-a-chip cultures are minimal [ 28 , 32 ]. For this reason, it is necessary to develop alternative methodologies for local delivery in fluidic chips for brain slice evaluation without depending on a flow.…”
Section: Introductionmentioning
confidence: 99%
“…Specific reagents, such as pharmacological agents or fluorescent dyes, can be dissolved in the reservoir fluid, either by not reaching their optimal concentration or by constantly exposing brain slices to these stimulations. There are brain-on-a-chip devices [ 29 , 30 , 31 ] focused on localized drug application for brain-on-a-chip, but the alternatives for this application in brain slice-on-a-chip cultures are minimal [ 28 , 32 ]. For this reason, it is necessary to develop alternative methodologies for local delivery in fluidic chips for brain slice evaluation without depending on a flow.…”
Section: Introductionmentioning
confidence: 99%
“…PDMS can be made in different shapes to fit biological tissues. Moreover, its mechanical impedance matching property to soft tissues such as the spinal cord and the oxygen-permeability make it one of the best MEA/neural tissue interfaces [13][14][15]. Other flexible substrate options include parylene-c [16,17], Ecoflex 00-30 [18], silicon elastomers like RTV-2 [19], and so on.…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4] By means of nano-and micro-technologies, the benefits of substrate-integrated extracellular electrode arrays are being combined with those of intracellular electrodes to improve the quality and performance of neural interfaces. [1,5] Importantly, nanotechnology allows for an improved design of lower impedance and a more intimate interface with individual neurons by better mimicking the native extracellular environment. [6] Early studies reported the ability of high-density silicon nanowire (NW) transistor arrays to record signals from up to 50 different spatial points in a single axon.…”
Section: Introductionmentioning
confidence: 99%
“…[17] Aiming to biomedical applications, the flexibility of the electrodes becomes an essential factor to minimize the mechanical mismatch at the interface and guarantee an effective coupling. [5] In this line, a series of flexible electrodes have been proposed, [18][19][20] but only a few combine flexibility with nanostructure. [21,22,23] For instance, Rogers and colleagues described a bio-interfaced system based on ultrathin electronics supported by bioresorbable substrates of silk fibroin, [18] which assures minimal stresses on the tissue and highly conformal coverage.…”
Section: Introductionmentioning
confidence: 99%